Management of Educators and Education Personnel in Improving the Quality of Education at PAUD Miftahussalam Seluma - Indayani, Yantik; Haryono, Mimpira; Margaretha, Lydia (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
This research aims to describe how educators and education staff manage to improve the quality of education at PAUD Miftahussalam Seluma Regency. This research is a qualitative descriptive research which has the meaning of describing a research that is being carried out. The main subjects in this research were the head of PAUD Miftahussalam and 7 teachers totaling 8 people. Research Instruments This research uses primary data (including observations and interviews of the Head of PAUD and teachers at PAUD Miftahussalam) and secondary data (including important documents). Data collection techniques in this research used observation, interviews and documentation methods. The data analysis technique in this research goes through three stages, namely data reduction, data display, and concluding. Data analysis was carried out descriptively qualitatively with emphasis on efforts to answer research questions through formal argumentative thinking. This research concludes that the management of educators and education personnel in improving the quality of education in Miftahussalam PAUD Seluma district has been implemented starting from planning, recruitment, job placement, and coaching and development, but has not been carried out optimally on a routine and continuous basis.Key Words : Management Education Personnel, Quality of Education.